Users’ perceptions of electronic patient safety incident reporting software - Koskiniemi, Saija; Syyrilä, Tiina; Mikkonen, Santtu; Hämeen-Anttila, Katri; Härkänen, Marja (Finnish Journal of eHealth and eWelfare, 2024)
Incident reporting is a central part of the continuing development work on client and patient safety, although incidents are under-reported. At the general level, it is known that incident reporting systems themselves can be one of the many reporting barriers. Nevertheless, users’ perceptions of incident reporting systems and their features, in addition to users’ knowledge regarding incident reporting, have not been widely studied. This study describes users’ perceptions and knowledge of patient safety incident reporting software and incident reporting. The results can be used when planning and developing incident reporting processes and systems. The study was conducted as a cross-sectional electronic survey. The questionnaire was sent to all potential incident software users in two wellbeing service counties in Finland in January 2024. From the data, HaiPro and Laatuportti systems’ users’ (n=729) background questions and structured responses were analysed. The results were presented as frequencies, percentages, means, and standard deviations. Differences between HaiPro and Laatuportti users’ satisfaction were investigated using the Mann-Whitney-U-test. The results showed that the respondents were satisfied with their knowledge related to incident reporting and reporting software. Respondents were the most dissatisfied with the features of incident reporting software for handling the reports. There were no statistical differences between HaiPro and Laatuportti users’ responses. However, HaiPro users were often more satisfied with the software’s features than Laatuportti users. Altogether, respondents were similarly satisfied and dissatisfied with the reporting software’s features, regardless of the software used. In Finland, incident reporting software reform is planned based on the national Client and Patient Safety Strategy and its Implementation Plan. In this development, attention to end-users’ perceptions is central to achieving improved software acceptance and effective implementation.